Calibration of polydimethylsiloxane and XAD-Pocket passive air samplers (PAS) for measuring gas- and particle-phase SVOCs. (October 2016) - Okeme, Joseph O.; Saini, Amandeep; Yang, Congqiao; Zhu, Jiping; Smedes, Foppe; Klánová, Jana; Diamond, Miriam L.
Abstract: Polydimethylsiloxane (PDMS) has seen wide use as the stationary phase of gas chromatographic columns, a passive sampler in water, and recently as a personal exposure sampler, while styrene divinyl-benzene copolymer (XAD) has been used extensively as a passive air sampler outdoors and indoors. We have introduced PDMS and XAD-Pocket as new indoor passive air samplers (PASs). The XAD-Pocket was designed to maximize the surface area-to-volume ratio of XAD and to minimize obstruction of air flow by the sampler housing. Methods were developed to expedite the use of these PASs for measuring phthalates, novel brominated flame-retardants (NFRs) and polybrominated diphenyl ethers (PBDEs) indoors. Sampling rates, R s, (m 3 day −1 ), were measured during a 7-week calibration study. Variability within and between analyte groups was not statistically significant. As a result, generic values of 0.8 ± 0.4 and 0.5 ± 0.3 m 3  day −1  dm −2 are recommended for PDMS and XAD-Pocket for a 50-day deployment time, respectively. PDMS has a higher uptake rate and is easier to use than XAD-Pocket. Highlights: PDMS and XAD-Pocket presented as indoor passive air samplers. Both PASs calibrated for measuring phthalates, NFRs and PBDEs indoors. R s of 0.8 ± 0.4 and 0.5 ± 0.3 m 3  day −1  dm −2 for PDMS and XAD-Pocket, respectively. PDMS has a higher uptake rate and greater ease of use than XAD-Pocket.